Perceptions, Behaviors and Food habits of Young Generation in Brahman Community: A Case Study from Kathmandu Valley - Mithu, Regmi (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Eating behavior is strongly influence by social setting, time convenience, norms, values and personal preferences as well. Age is the most important determinant factors of food choice. So in this paper I have discussed about food choices of young generation among Brahmans social group. information was collected during my fieldwork of MPhil dissertation in 2014 by using ethnographic methodology. I have used qualitative data only. During my fieldwork, most of the young generation told that they do not believe on cast-based food ideology but at home they follow the minimum rules related to food.